Kontribusi Sektor Pariwisata terhadap Pendapatan Asli Daerah Kabupaten Mamasa - Hermin Hermin; Natalia Paranoan; Sita Y. Sabandar (Jurnal Syntax Admiration, 2024)
This study aims to examine the contribution, revenue growth, and effectiveness of tourism sector revenue to Mamasa Regency's Regional Original Revenue (PAD) in the 2019-2023 period. Researchers used a qualitative descriptive method with analysis of contribution ratios, growth ratios, and effectiveness ratios. The results showed that the contribution of the tourism sector to Mamasa Regency PAD was still relatively low, with an annual average of 69.26%. The lowest contribution occurred in 2020 at 6.23%, while the highest contribution was recorded in 2023 at 18.59%. The highest tourism sector revenue growth was recorded in 2021 at 125.63%, and the lowest in 2020. The level of effectiveness of tourism sector revenue during 2019-2023 is included in the highly effective category, with an average of 123.12% per year.